Stopped‐Flow 19F NMR Spectroscopic Analysis of a Protodeboronation Proceeding at the Sub‐Second Time‐Scale. Issue 17 (5th May 2021) - Wei, Ran; Hall, Andrew M. R.; Behrens, Richard; Pritchard, Mark S.; King, Edward J.; Lloyd‐Jones, Guy C.
Abstract: In‐situ NMR spectroscopic analysis of homogeneous reactions is an essential tool for mechanistic analysis in organic and organometallic chemistry. However, rapid non‐equilibrium reactions, that are initiated by mixing, require specialized approaches. We report herein on a study of the factors that ensure quantitative results in a recently‐developed technique for stopped‐flow NMR spectroscopy. The influence of some of the key parameters on quantitation is studied by 19 F NMR spectroscopic analysis of the kinetics and activation parameters for the base‐catalyzed protodeboronation of highly‐reactive polyfluorinated arylboronic acids, with half‐lives as low as 0.1 seconds. The effects of spin relaxation, pre‐magnetization, heat‐transfer versus reaction enthalpy, and mixing‐efficiency are analyzed in detail. We also compare and contrast choice of pulse angle, interscan delay, and use of pseudo real‐time by interleaving, as means to achieve an optimal balance between temporal resolution and sensitivity. Abstract : The protodeboronation of a reactive boronate has been analyzed by stopped‐flow 19 F NMR spectroscopy. The study shows how the consideration of longitudinal relaxation, pre‐magnetization, mixing, heat transfer, pulse angle, interscan delay, and spectral interleaving, allows the kinetics of a reaction with a half‐life of 0.12 seconds to be measured by NMR.